Articulate Storyline 3 Media to Improve Learning Outcomes in Natural and Social Sciences Subjects in Fourth-Grade Elementary School - Pambudi, Chandra Tri; Ratnaningrum, Ika (International Journal of Elementary Education, 2024)
The lack of utilization and varied use of learning media means that student learning outcomes have not been achieved optimally in Natural and Social Sciences subjects in grade IV elementary schools. This research aims to create a product in the form of Articulate Storyline 3 which is used as a learning medium for Natural and Social Sciences subjects, and material about cultural diversity in Indonesia. The type of research used is Research and Development with the ADDIE development model. The subjects in this research included media experts, material experts, teachers, and 28 fourth-grade elementary school students. Data collection in this research took the form of test techniques and non-test techniques. Test techniques use pretest and posttest, while non-test techniques use observation, interviews, questionnaires, and documentation. Furthermore, the data analysis techniques used were the normality test, t-test, and N-Gain test which were processed using the SPSS 23 application. The N-Gain test in small-group trials and large-group trials obtained values of 0.60 and 0.64 in the medium category, so it was concluded that there was an increase in the average student pretest and posttest scores. Thus, this research concludes that the Articulate Storyline 3 media is very suitable and effective for use in improving student learning outcomes on cultural diversity material in Indonesia in class IV elementary schools.